2017
DOI: 10.1016/j.fertnstert.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of amnion in creation of neovagina in women with Mayer-Rokitansky-Kuster-Hauser syndrome

Abstract: In a developing nation like India, McIndoe's method with amnion graft seems to be a promising option owing to its low cost, easy availability, and safety, ease of the procedure not requiring any special instrument, physiologic outcome with respect to epithelialization of the vagina without hair growth, and satisfying functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Akle et al (1981) found no evidence of infections since the amnion has an antibacterial effect. Vatsa et al (2017) performed an analysis in 50 patients with vaginal agenesis that were submitted to neovaginoplasty with amnion. All patients obtained successful results with vaginal length and sexually active life.…”
Section: Discussionmentioning
confidence: 99%
“…Akle et al (1981) found no evidence of infections since the amnion has an antibacterial effect. Vatsa et al (2017) performed an analysis in 50 patients with vaginal agenesis that were submitted to neovaginoplasty with amnion. All patients obtained successful results with vaginal length and sexually active life.…”
Section: Discussionmentioning
confidence: 99%
“…Small intestine mucosa, absorbable adhesion barrier, buccal mucosa, amnion membrane, peritoneum, tilapia fish skin, in vitro cultured vaginal tissue are the published materials that were used to create a vagina. [4][5][6][7][8][9][10][11] This technique has a short recovery period because of not involving any abdominal process. However, using graft materials increases the cost of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The first approach is the Mc Indoe method 3 , a vaginal surgery consisting of insertion a created vagina (with numerous materials like an autologous skin graft, invitro cultured vaginal tissue, acellular collagen, amniotic membrane, fish skin, buccal mucosa) into the dissected pouch between rectum and bladder. [4][5][6][7][8][9][10][11] The second approach is the Vechietti operation which requires long-term abdomen-vaginal traction with special instruments. [12][13][14] This method is including both vaginal and abdominal (laparotomy or laparoscopy) surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Puede además cursar concomitantemente con otras alteraciones tales como anormalidades renales en el 40% de las pacientes y anormalidades esqueléticas en el 10-15% de los casos 8 .…”
Section: Introductionunclassified
“…Múltiples procedimientos quirúrgicos y no quirúrgicos han sido descritos, los cuales tienen como objetivo la creación de una neovagina de tamaño y condiciones fisiológicas adecuadas que permitan una función cotial normal, sin embargo, el método y el injerto ideal aun son debatidos 5,8,10,11 .…”
Section: Introductionunclassified